Intergenerational redistribution, health care and politics - Douglas Lundin; María Sáez Martí (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
Publicly provided health care implies considerable intergenerational redistribution. The possibility of accumulating a fund or debt will affect the degree of redistribution as well as how efficient the financing of health care is. In a voting model we study how governments inability to make binding long-term policy commitments will affect the accumulation of a fund or debt. Today's government will base its policy decisions on expectations about future governments behavior and simply follow suit, which results in strong political inertia. Either a fund or debt may therefore be upheld in political equilibrium. But no mechanism ensure that it is at its optimal level. If there is fund in steady state, the more political clout the old have the smaller will the fund be, i.e saving decrease. If there is debt, however, a politically stronger old generation may imply a smaller debt, i.e. savings increase.
Keywords: D78; H55; I10; 330; Voting; health expenditure; intergenerational transfers; dynamic politics; Gesundheitskosten; Intergenerative Belastungsrechnung; Generationenbeziehungen; Verteilungstheorie